Anomalous growth of the complex carbide phase in carbon-deficient WC-Co hard metal during the infiltration of eutectic liquid - 박종구; 은광용; 윤덕용 (ELSEVIER SCIENCE, 1988)
During infiltration of the carbon-deficient 97WC-3Co bodies with 25WC-75Co infiltrants (where the compositions are in weight per cent), some large grains (about a few hundreds of micrometers in size) of η phase (Co